Contraceptive methods: Prevalence rate and characterization in women of the Eje Cafetero, Colombia, 2016-2019 - Espitia, Franklin De La Hoz (2020)
Objective: To determine the prevalence and characterize contraceptive methods in women of the Coffee Region, and to establish the adverse effects of hormonal methods. Materials and methods: Cross-sectional study. 1875 women over 18 years of age, sexually active and residing in the Coffee Axis were included. The research was carried out in the gynecology outpatient clinic of six hospital institutions (public and private), in the 6 main cities of the Coffee Region (Armenia, Calarcá, Pereira, Dos Quebradas, Manizales and Chinchiná); between July 2013 and June 2019. Descriptive analysis was performed. A stratified description is made by age from 18 years. Results: Age showed an average of 26.45 ± 3.72 years. The prevalence of contraception - family planning in the women of the Coffee Region is 78.24%. Hormonal methods are the most used (69.12%), followed by sterilization (19.23%). Among the hormonal ones, the oral ones are the most used (60.05%) and secondly the implants (24.26%). Mastalgia is the main adverse effect (32.92%) followed by acne (27.19%). Altered sexual function occurred in 7.39% of users of hormonal methods. Conclusions: about las parts of women in the Coffee Region use a contraceptive method, with hormonal methods being the ones of choice in las of the population, with ⅓ of adverse effects that do not affect the satisfaction rate.